Road traffic accidents; An observational and analytical study exploring the hidden truths in Pakistan and South East-Asian Countries - Tabish Hussain1, Li Yu Shu; Tumenjavkhlan Sosorburam; A.Seid Adji; Ali Hassan Khan; Asim Farooq Raja (Healthline, 2011)
Despite national traffic legislation and known safety benefits of traffic laws, awareness remains low in Pakistan. Study aim was to determine level of knowledge about traffic legislation and attitudes towards their observation in capital city Islamabad to provide baseline data for formulation of an intervention aimed at strengthening road safety law enforcement. Survey-Analysis with Random Observational study was conducted by using standard survey questionnaire focusing Roadsafety awareness levels and use of helmets/seatbelts on MainRoads and StreetRoads.Drivers/passengers/pedestrian were randomly selected to participate in face-to-face interview to ascertain attitudes. Overall, Deficient Road-Safety Awareness was at top(27%)followed by wrong use/no use of seatbelts/helmets(21%) and legislative aspects were at last(17%)including under-age driving,vehicles without fitness and licensure problems exploring the bitter hidden truths. Actions areas for preventing Road Traffic Accidents(RTAs) include interventions to improve road-safety education, identification /implementation of safety measures for traffic black-spots, enforcement of seatbelt/helmet laws and the development of highway ordinances. PRECAUTION IS BETTER THAN CURE as Road Traffic Accidents are 100% preventable.